Radioactive Gamma-Ray Emissions from Neutron Star Mergers - Li, Li-Xin (The Astrophysical journal, 2019)
Gravitational waves and electromagnetic radiations from a neutron star merger were discovered on 2017 August 17. Multiband observations of the optical transient have identified brightness and spectrum features broadly consistent with theoretical predictions. According to the theoretical model, the optical radiation from a neutron star merger originates from the radioactive decay of unstable nuclides freshly synthesized in the merger ejecta. In about a day the ejecta transits from an optically thick state to an optically thin state owing to its subrelativistic expansion. Hence, we expect that about a day after the merger the gamma-ray photons produced by radioactive decays start to escape from the ejecta and make it bright in the MeV band. In this paper, we study the features of the radioactive gamma-ray emission from a neutron star merger, including the brightness and the spectrum, and discuss the observability of the gamma-ray emission. We find that more than 95% of the radiated gamma-ray energy is carried by photons of 0.2-4 MeV, with a spectrum shaped by the nucleosynthesis process and the subrelativistic expansion of the ejecta. Under favorable conditions, a prominent pair annihilation line can be present in the gamma-ray spectrum with the energy flux about 3%-5% of the total. For a merger event similar to GW170817, the gamma-ray emission attains a peak luminosity of 2 × 1041 erg s−1 at 1.2 days after the merger and fades by a factor of two in about 2 days. Such a source will be detectable by satellite-ETCC if it occurs at a distance 12 Mpc.